The Use of Writing Personal Letter in Teaching Recount Text for the Eighth (RETAIN, 2014)
The Use of Writing Personal Letter in Teaching Recount Text for the Eighth Choirun Nisaa English Education, Languages and Arts Faculty, State Unuversity of Surabaya Choirerunni@ymail.com Dosen pembimbing Him’mawan Adi Nugroho, S.Pd., M.Pd English Education, Languages and Arts Faculty, State University of Surabaya Abstrak Penelitian ini mengkaji tentang penggunaan menulis surat pribadi dalam pengajaran teks recount untuk siswa kelas delapan. Guru EFL sering menempatkan pengajaran menulis pada urutan terbawah prioritas mengajar. Bagaimanapun juga, belajar menulis itu penting bagi siswa. Masalah utama yang dihadapi siswa dalam menulis adalah kebosanan. Guru EFL harus meninggalkan cara yang biasa dalam pengajaran menulis dan mencoba untuk memberikan cara kreatif untuk hal ini. Penelitian ini memiliki dua pertanyaan penelitian; (1) bagaimana penerapan menulis surat pribadi dalam pengajaran teks recount untuk siswa kelas delapan? Dan (2) bagaimana tanggapan siswa pada penerapan menulis surat pribadi dalam pengajaran teks recount? Penelitian ini adalah penelitian deskriptif kualitatif. Subyek dalam penelitian ini adalah guru dan siswa kelas VIII D SMP Bahrul Ulum Suranbaya. Instrumen yang digunakan dalam penelitian ini adalah lembar observasi, catatan lapangan, karya siswa, dan kuesioner. Hasil penelitian menunjukkan bahwa pengajaran menulis teks recount mengunakan menulis surat pribadi bisa menarik memunculkan keinginan siswa untuk belajar teks recount. Hal ini di buktikan oleh kondisi dimana siswa aktif selama proses belajar mengajar. Hasil penelitian ini juga menunjukkan bahwa pengajaran menulis teks recount menggunakan menulis surat pribadi mendapat tangapan positif dari siswa. Kebosana dalam menulis yang sering dirasakan oleh para siswa dapat dikurangi. Selain itu, tanggapan positif ditunjukkan oleh hasil karya siswa. Siswa dapat menuangkan ide dalam tulisan mereka. Namun, siswa masih mengalami kesulitan berkaitan dengan tata bahasa. Sebagai kesimpulan, penerapan menulis surat pribadi dalam pengajaran teks recount berhasil diterapkan oleh guru. Hal ini dikarenkaan guru memilih materi yang sesuai dengan tingkatan siswa dan latar belakang pengetahuan siswa. Hal ini juga mendapat tanggapan positif dari siswa. Mereka setuju bahwa penerapan menulis surat pribadi dalam pengajaran teks recount dapat mengurangi kebosanan mereka dalam menulis. Tanggapan positif lainnya ditunjukkan pada hasil karya siswa. Siswa telah mampu menuangkan ide-ide mereka dalam tulisan mereka. Kata Kunci: menulis, teks recount, surat pribadi Abstract This study investigates on the use of writing personal letter in teaching recount text for the eighth graders. EFL teachers often put writing in the bottom list of priorities in teaching. However, writing is essential for teacher. The main problem that students faced in writing is boredom. EFL teachers should leave a conventional way of teaching writing and try to provide a creative way for teaching writing. This study has two research questions; (1) how does the application of writing personal letter in teaching recount text for the eighth graders? And (2) how are the students’ responses on the application of writing personal letter in teaching recount text? This study is a descriptive qualitative. The subjects are the teacher and the students of VIII D SMP Bahrul Ulum Surabaya. The instruments which are used in this research are observation checklist, field note, students’ work, and questionnaires. The finding of the study shows that teaching writing of recount text involving writing personal letter could attract students willing in learning recount text. It proved by the condition where students are active during the teaching and learning process. The finding also showed that teaching writing of recount text involving writing personal letter gets a positive response from the students. The boredom in writing that commonly felt by the students could be reduced. Moreover, the positive response is showed by the result of the students’ works. Students can deliver idea in their writing. However, students still have difficulty dealing with grammar. In conclusion, the application of writing personal letter in teaching recount text was successfully applied by the teacher. It was because the teacher chose an appropriate level of material and students’ input. It also gets positives responses from the students. They agree that it can reduce their boredom in writing. Another positive response is showed in the result of students’ works. Students have been able to deliver their ideas in their writing. Keywords: Writing, Recount Text, Personal Letter INTRODUCTION In Indonesia, English is taught as a Foreign Language (EFL). One of the purposes of teaching English at school in Indonesia is to develop students’ ability in communicating using English. Talking about communication ability, there are four skills that have been widely known, they are; listening, speaking, reading, and writing. In order to achieve the goal of EFL learning in Indonesia, These skills should be taught in an integrated way. Many studies on English Language Teaching in Indonesia show that the aim of learning English has never been satisfactorily achieved (Gunarwan, 2000). EFL teachers in Indonesia seem to have a misunderstanding on how English should be taught regarding to the goal of building the learners’ communication skills. They emphasize more on the oral skill, which is actually true in a sense. However, EFL teachers should not put aside the other three skills that are reading, writing, and listening. Listening and reading are categorized as a receptive skill. Receptive skills are the ways in which people extract meaning from the discourse they see or hear (Al-Jawi, 2010). On the other hand, speaking and writing are categorized as a productive skill. In productive skill students use the language that they have acquired and produce a message through speech or written text. It can be said that in productive skill students will be more active than in the receptive skill. It is the reason why people often say that productive skill is more difficult than receptive skill. Writing is a productive skill in a written form while speaking is a productive skill in a spoken form. Writing is a system for thinking process and interpersonal communication put on paper using visible signs or graphic symbols on a flat surface such as paper, cloth or even stone slab (Al-Jawi, 2011). Writing is also called as the ‘forgotten skill,’ it is because it receives the least attention of the teacher. Moreover teachers often put writing at the bottom list of teaching priorities. Some people are more comfortable to communicate in a written form but some others are good in communicating in a form of spoken. People often communicate through writing. This makes it necessary for the EFL learners to learn how to write (Al-Jawi, 2011). The majority of language learners consider the writing skill as one of the most challenging linguistic abilities to foster; indeed, teachers of writing often hear their students complain of uncertainty about how to express themselves in writing (Luchini, 2003). Writing as one of the four language skills is often considered as a difficult skill because the writer should pay attention to their content, organization, purpose, vocabulary, punctuation, and spelling. In writing, students often get difficulty dealing with grammar. As the result, they get serious difficulty in writing. It is also the reason why students get bored in writing. Teacher’s monotonous way of teaching writing also causes in students’ unwilling in writing. In teaching writing, teachers should be familiar with what writing is all about, why people write, what kind of things they write and for what purposes, what a writer of different kinds of writing needs in order to write successfully (Al-Jawi, 2011). Moreover, teachers should know the various stages in the development of writing skills, that is they need to know the main issues that concern teachers of writing so that they can make informed choices in their own practice as a teacher of writing. Helmi (2012) defines several problems that are mostly faced by students in writing, they are; (1) Limited vocabulary, (2) Difficulty in organizing to write about something, (3) No motivation to write, and (4) Lack of confidence in grammar. All of those problems brings the students become lazy in writing. It simply because they are afraid of have a bad writing even they do not have any idea to be written. As a nature, it is important for the teacher to help the students with the problem that students faced. As stated before, students’ boredom is one of the problems of teaching writing in the classroom. It is commonly happened when the teacher teach them in conventional way. Several efforts should be done to solve the problems in teaching writing. Teachers should be creative in designing their way of teaching. The purpose is to make writing becomes easier and more interesting for the students. When it is successfully done, it can attract students’ interest in learning writing. According to Ahlsen and Lundh (2007), many teachers use a rather monotonous way of working with writing. Students are often left on their own with a blank piece of paper and a pencil without many guidelines, inspiration or a defined purpose. From this poit, it is showed that EFL teachers still use conventional way in teaching writing. The thing that should be done by the teacher in teaching writing is that using some approaches, methodes, techniques, strategy, or even providing a classroom activity in the teaching and learning process. When the teacher is successful in doing it, the teacher can make writing become easier and more interesting to be learned by the students. There was a previous study that investigates on the implementation of writing personal letter in teaching recount text. That study observed EFL teacher that implemented writing personal letter in teaching writing. That study focused on the analyzing students’ ability in producing recount text as the result of the implementation of writing personal letter. Another study investigated on the use writing personal letter for teaching narrative text. It was the same with the study that stated before. The deference appears on the text that was taught. This study focuses on the teaching writing of recount text for the eighth graders as stated in Standar Isi (2006), ‘Mengungkapkan makna dan langkah retorika dalam esei pendek sederhana dengan menggunakan ragam bahasa tulis secara akurat, lancar dan berterima untuk berinteraksi dengan lingkungan sekitar berbentuk recount.’ Recount text is a kind of text that tells a story of certain experience. The communicative purpose of the text is to retell events as information or entertainment. The generic structures of recount text are; (1) Orientation, (2) Series of Events, and (3) Reorientation (Standar Isi, 2006). Past tense is used in writing a recount text because it tells a story of a certain experience, which means that the events happened in the past. According to Hyland (2004) cited from Helmi, Recount is a kind of genre that has social function to retell event for the purpose of informing or entertaining. Social purpose of recount is to reconstruct past experiences by retelling events in original sequence. The researcher has conducted a pre-observation to decide the subjects of the study. From the pre-observation, the researcher found EFL teacher who uses writing personal letter in teaching recount text. This teacher teaches the eighth graders. The teacher argued that by providing an interesting writing activity which is writing personal letter activity in teaching writing of recount text, students will be more interested in learning it. Personal letter is a missive communication in writing, addressed to a person or body of person (Bodomo, 2003). According to Stockwell (1981) cited from Suryowati , a personal letter consists of private information about people and things to a certain people in the written form. A personal letter is also called as a private letter. It contains of private information about personal experience in the written form to be sent in a certain people. Another Kompetensi Dasar of Standar Isi (2006) stated ‘Mengungkapkan makna dalam bentuk teks tulis fungsional pendek sederhana dengan menggunakan ragam bahasa tulis secara akurat, lancar dan berterima untuk berinteraksi dengan lingkungan sekitar.’ ‘Teks fungsional pendek’ includes Personal letter. This Kompetensi dasar is in the same Standar Kompetensi with Kompetensi Dasar of recount text. In conclusion, it is the evidence that personal letter id taught for the eighth graders. Personal letter is one of the examples of writing product that can be used as media to interact, sharing experiences and to communicate each other in written form personally (Helmi, 2012). Bodomo (2003) defines the structure of personal letter, they are; (1) Date, (2) Salutation and name of recipient, (3) Introduction, (4) Body, (5) Closure, (6) Complimentary Close, and (7) Signature. From the explanation before, it is known that recount text and personal letter; (1) telling about past events, (2) telling sequence of events, and (3) telling about someone’s experience. The orientation part of recount text is called as salutation in personal letter, the events part of recount text is called as body in personal letter, and reorientataion of recount text is called as closing in personal letter. From this point, the teacher argued that recount text could be written in a form of personal letter. In conducting the teaching and learning process of recount text involving writing personal letter, firstly the teacher explains about recount text. The explanation about recount text includes the generic structures, the tense that is used, also the language features of it. The next step is he explains about personal letter. He shows that recount text and personal letter have similarities. Therefore, recount text could be written in a form of personal letter. In the end of the explanation, the teacher conducts a classroom writing activity involving writing personal letter that tells about students’ personal experience. Students are put in a condition where they are supposed to send some personal letters for their close friend, family, etc. the teacher believes that by doing this, students will be more interested in the classroom writing activities. The investigation on how the use of writing personal letter in teaching recount text is developed by the researcher into research questions: How does the application of writing personal letter in teaching recount text for the eighth graders? How are the students’ responses on the application of writing personal letter in teaching recount text? Related to the research questions, the objectives of the study can be presented as follows: To describe the result of the application of writing personal letter in teaching recount text for the eighth graders. To describe the students’ responses on the application of writing personal letter in teaching recount text. By doing this study, which is the use of writing personal letter in teaching recount text, the finding will show that the theory used in this study can be applied in the teaching of EFL in Indonesia. Moreover, it is also expected that the finding of this study can inspire teachers in designing and improving their teaching activities related to the theory in this study. It is also expected that writing personal letter activity can attract the students’ interest in composing their own recount text and thus can increase the students’ ability in writing recount text. METODE This study focused on the use of writing personal letter in teaching recount text that was done by EFL teacher. Students’ work of recount text was analyzed, and also students’ responses toward the application in the teaching learning process were collected. This study relied mostly on the teacher’s performance in using writing personal letter in teaching recount text in his EFL classroom. Thus, a descriptive qualitative research design was chosen for the researcher described how the process of the application itself. Qualitative research has four purposes: exploration, explanation, description, and prediction (Marshall and Rosman, 1995, cited in Wilson). According to marshal and Rossman (1999), the purpose of a qualitative research is “to stress the unique strength of the genre for the research that is exploratory or descriptive, that assumes the value of context and setting, and that searches for a deeper understanding of the participant’s lives experiences of the phenomenon.” It was in line with the purpose of the researcher in conducting this study, which was to search for a deeper understanding on the application of using writing personal letter in teaching recount text in EFL classroom. The subjects of the study were the teacher and the students of SMP Bahrul Ulum Surabaya. The students were the eighth graders of Junior High School exactly students of VIII D SMP Bahrul Ulum Surabaya. They were supposed to learn recount text for their writing material in the first semester. The teacher used writing personal letter in teaching recount text to attract students’ interest in learning it. It also used to encourage students’ willing in composing their own recount text. The teacher believed that this activity could reach the goal of his EFL classroom. This study was conducted in SMP Bahrul Ulum Surabaya which was located in Putat Jaya Sekolahan 11-13 Surabaya. This school was chosen since the teacher used writing personal letter in teaching recount text in the EFL classroom. This school had implemented KTSP curriculum which gave the school authority in designing the syllabus based on the school visions and missions. The researcher was the key instrument of this study. The researcher used four instruments in collecting the data, they were; (1) Observation checklist, (2) Field-note, (3) student’s work, and (4) Questionnaire. Basically, there are two types of observation, they are; participatory observation and non-participatory observation. In a participatory observation, the researcher would take a part and participate in the teaching learning process where the research is done. While in non-participatory observation, the researcher would not take a part and participate in the research or the teaching learning process. The researcher would only sit in the back of the class and observe the teaching and learning process. In this study, the researcher had non-participatory observation where researcher was not the one who did the teaching learning process. In conducting an observation, the researcher absolutely needed two kinds of observation’s instrument, which were observation checklist and field-note. For field-note would be explained more in the next explanation. Observation checklist was a list of things which were observed by the researcher. It was noticeable that the list must contain points that were related to the problem of this study, so that the research questions of this study could be answered by the result of the observation itself. In line with the problem of this study, the researcher had several focuses to be included in the observation checklist; they were (1) Teacher’s role, (2) Students’ role, (3) Interaction, and (4) the application of writing personal letter in teaching recount text. As explained in the previous explanation, another observation’s instrument which was helpful in conducting an observation was field-note. Field-note used to note everything which happened during the observation that was important for the study. It considered that field-note covered things that were not included in the observation checklist. Field-note contained two kinds of material, which were descriptive materials and reflective materials. While observing the teaching learning process, the researcher recorded the activities done in the descriptive part of the field-note. At the same time, the researcher filled in the reflective part of the field-note with the researcher’s comments on the teaching learning process. In the end of the application of writing personal letter in teaching recount text, the teacher asked students to compose their own recount text in a form of personal letter. Then teacher analyzed students’ work by using ESL composition profile. There were several aspects that contained in ESL composition profile that was designed by Jacob (1981), They were (1) Content aspect, (2) Organization aspect, (3) Vocabulary aspect, (4) Language Use aspect, and the last one (5) Mechanics aspect. Content aspect was about ideas of students’ work which was recount text. Organization aspect included the compatibility between the students’ writing and generic structures of recount text. Vocabulary aspect analyzed the word choice of students in composing recount text. Language aspect focused on the grammatical used by students in composing recount text, for example the use of past form. Mechanic aspect included the writing of word spelling, punctuation, and capitalization that was used in the recount text. Questionnaire contains questions used to gain information from respondents. There are two types of questionnaire; they are structured questionnaire and unstructured questionnaire. Structured questionnaire has a number of questions with limited choice of answers. The purpose of administering is to get fact. While in unstructured questionnaire, there are also a number of questions but the answers are in the form of essay, so the content of the answer may different and also vary among the respondents. The purpose of administering this kind of questionnaire is to explore something. The structured questionnaire was used by the researcher with aim to avoid a broad answer from the students. However, by doing this, the researcher still could explore the students’ experiences of the application of writing personal letter in teaching recount text. The content of the questionnaires was about the students’ opinion on the teaching learning process. Three different qualitative data were compiled to be used for answering the research questions. The data of this study were in the form of; (1) check points in the researcher’s observation checklist, (2) words written in the researcher’s field-note, (3) words written of students’ work of recount text, and (4) the answers chosen by the students in the questionnaires. The sources of the data were; (1) observation that was done in the classroom teaching learning process, where researcher observed the application of writing personal letter in teaching recount text, (2) students’ works of recount text which were analyzed using the ESL Composition Profile (Jacob, et.al., 1981), and also (3) The questionnaires given to the students, which gave information about students’ responses to the teaching and learning process. In line with the research instruments used in this study, the researcher applied three techniques in collecting the data, they were; (1) doing the observation, (2) collecting students’ work, and the last was (3) giving a questionnaire. As explained before, this research was designed as a descriptive qualitative research. Thus, the researcher was a non-participatory observer. The researcher only observed the teacher when he was conducting the teaching learning process. In the first day of the observation, the teacher taught about simple past tense. It was done as pre-material before he taught recount text. In the second day of the observation, the teacher taught recount text involving writing personal letter. During the teaching and learning process, the researcher filled the observation checklist. Besides, the researcher also used field-note to take notes of things that may support the data collected through the observation checklist. It took a whole duration of teaching for the explanation, so that the activity of writing recount text was done in the next meeting. In the last day of observation, students were asked to compose recount text in a form of personal letter. ESL Composition Profile was used to analyze; (1) the content, (2) the organization (3) the vocabulary, (4) the language use, and (5) the mechanic of the students’ work. In the end, the researcher gave questionnaires to the students which gave information to the researcher about students’ responses to the application of writing personal letter in teaching recount text. To analyze the data of the study, the researcher read all the data gathered from the observation checklist, field-note, students’ work, and questionnaire. The data gathered through observation checklist and field-notes were analyzed descriptively. The result of observation checklist and field-notes were then compiled to give information to the researcher about teacher’s idea in the use of writing personal letter in teaching recount text. And also the data gave information to the researcher about the problems that occur during the application of writing personal letter in teaching recount text. Other than from the teacher, the researcher also gathered information from the students who involved in the application of writing personal letter in teaching recount text. The data gathered from questionnaires given to the students gave information about their responses toward the application of writing personal letter in teaching recount text. By doing this, the researcher had the idea whether their responses were as expected by the teacher or not. The result of students’ works completed the finding of the research. It gave information to the researcher the students’ quality in composing recount text as a result of the application of writing personal letter in teaching recount text. After analyzing all the data, the researcher had organized information about the use of writing personal letter in teaching recount text (how the way of the application, the result of students’ work, and students’ responses toward the application). These would be discussed further in the next chapter. RESULT OF CLASSROOM OBSERVATION In conducting the classroom observation, the researcher used two instruments, which were observation checklist and field notes. The classroom observation was conducted in three meetings regarding to the materials being learned, that was recount text. In the previous sub-chapter, the researcher has elaborated the result of the observation checklist and also field notes. Here, the researcher would analyze the result in order to get the answer for the first research questions of the research which is the result of the application. As explained in the previous sub-chapter about the result of observation checklist and also field notes, there are two points that should be investigated. The first point is about the application of writing personal letter in teaching recount text. The second point is the use of English during the teaching and learning process. Starting with the first point, the researcher would investigate the application of writing personal letter in teaching recount text. As elaborated in the previous chapter, recount text was included in the KD of the second grade of Junior High Scholl exactly for the second semester. “Mengungkapkan makna dan langkah retorika dalam esei pendek sederhana dengan menggunakan ragam bahasa tulis secara akurat, lancar dan berterima untuk berinteraksi dengan lingkungan sekitar berbentuk recount.” Moreover, personal letter also included in the same SK with recount text but they are in the different KD. “Mengungkapkan makna dalam bentuk teks tulis fungsional pendek sederhana dengan menggunakan ragam bahasa tulis secara akurat, lancer dan berterima untuk berinteraksi dengan lingkungan sekitar.” Personal letter is included in ‘teks tulis fungsional pendek’.In conclusion, it was true that recount text and personal letter are taught in the first semester of eighth graders. In this study, the teacher asked the students to write a recount text in a form of personal letter. He argued that recount text and personal letter are the same in (1) structures, and (2) tense that is used, so that recount text could be written in a form of personal letter. He provided a different way of learning recount text which was by writing it in a form of personal letter. Writing personal letter activity is the activity in which the students write a personal letter about their own personal experience (Stockwell, 1981, cited in Hendriawati). It is in line with recount text where it also tells about personal experience. During the observation, the researcher noticed that the teacher seemed was easy to make students were willing in composing their recount text. The researcher believed that it was because the teacher provided an interesting way in learning recount text which is writing it in a form of personal letter. The teacher had thrown away the monotonous and boredom of writing class by using writing personal letter in teaching recount text. A good condition of teaching and learning process had been created by the teacher. Both teacher and students were interested to be active during the teaching and learning process. It was showed where students delivering several questions related to the teacher’s explanation. It seemed that they were motivated to learn about recount text especially producing it in a form of personal letter. Moving on the second point, the researcher would investigate about the use of English during the teaching and learning process. Since it was an English class, the researcher considered that it was important to investigate this point. The researcher found that the teacher used both English and Bahasa in the teaching learning process. The researcher noticed that it was difficult for the teacher to use full English in the class since most students had less ability in English. The condition that explained before does not mean that the teacher did not encourage the students to use English in the class. The teacher delivered the explanation in English and repeated it in Bahasa. Also for the instruction given was done in English and then repeated in Bahasa by the teacher. However, the teacher tried to stimulate students to use English by always saying something in English and repeating them in Bahasa. Moreover, the teacher also translating the students’ saying in English in order to make students know how to say that in English. RESULT OF STUDENTS’ RESPONSES The last result to be discussed was got from the questionnaires and the students’ works. The discussion on the result of the questionnaires and students’ responses would give an answer to the last research question. Unfortunately, there were 4 students were absent in the last day of the observation. Therefore, the researcher could not have a complete stack of answered questionnaires also students’ works. The questionnaires were divided into two focuses. The first focus was on the students’ opinion toward the application of writing personal letter in teaching recount text. The next focus was on the students’ opinion toward the advantages of the implementation of writing personal letter in teaching recount text. The result of the first focus showed that students were all interested in the teaching learning process involving writing personal letter that was done by the teacher. It proved by the condition where students were willing to involve in the writing activity and also compose their own recount text. Moreover, the teacher kept on encouraging the students to use English in the class by accustoming them to say common greetings and simple utterances in English rather than by forcing them to speak in English fully. The result for the next focus was also good. Students agreed that learning and composing recount text through writing personal letter was such kind of interesting way in learning it. It was not only interesting but also it was easier to be understood. It proved by the result of the students’ work where students had been able to write recount text with complete generic structures and also good content. Therefore, it can be considered more effective than a conventional way of teaching and learning recount text. The result of analysis toward students’ work would be discussed to support the result that was got from the questionnaires. As explained before that there were five aspects that had been scored toward students’ work. There would be a conclusion for each aspect’s result later on. For the first aspect was the content of students’ work. Knowledgeable, originality, accuracy, unified, good development of main idea, and also relevancy to the topic were the points that were scored. The result of analyzing was satisfying. Most of students were able to deliver their idea in composing their recount text in a form of personal letter. The researcher believed that it could be happened because the teacher was good in choosing the topic of the recount text which was about students’ personal experience. Students were interested in doing it since it was easy enough for them. The second aspect was the organization of students’ work. It measured the suitability of students’ writing toward the generic structures of recount text. Moreover, the sequence idea in each part was analyzed here. The result of the analysis was satisfying. Most of students were able to compose their recount text in a form of personal letter with complete generic structures. Most of the also could deliver a sequence idea in their writing. However, students still faced a problem about grammatical order. The third aspect was the vocabulary used by the students. It focused on analyzing word choice of students’ work. It was done since when students were wrong in using it, it could result in the changing of meaning. It was found that there were several students used common verbs but they put it not in proper way. The result was confusing meaning of their sentence. Several students also used unfamiliar words to their level but they did not know the exact meaning of it. That is why, they were wrong in arranging sentences using this words. Moreover, the researcher noticed that grammatical problem was still appeared in their work. The fourth aspect was the language used of students’ work. It focused on the grammatical used, they were; the use of past form and pronoun. The result of analyzing was poor. There were many students that still had difficulty in producing past form and using a correct pronoun. The researcher believed that the root problem of this phenomenon was the students’ understanding of past tense form. With the time, the researcher hoped that students could master this kind of grammatical pattern. The last aspect was mechanic of students’ work. It focused on the writing of past form, spelling, punctuation, capitalization, paragraphing, and also handwriting. The result was good enough. Most students were able to write every single word correctly. The problem just appeared in the punctuation and also capitalization. As the researcher observed, students still needed more practicing on how arrange a good paragraph. These problems could be solved by regular practice. Finally, the researcher could conclude that the result of students’ work of writing recount text in a form of personal letter was good. Students were able to composing a good recount text in a form of personal letter. Common problems that were faced by the students such as; grammatical errors and paragraphing could be solved by regular and also intensive practice. CONCLUSION In conclusion, the aim of using writing personal letter in teaching recount text is to reduce students’ problem in writing which is boredom. The teacher believes that by creating a condition where the students are supposed to write a letter to someone can make them being willing to compose recount text. In this case the teacher leaves a conventional way of teaching writing and applied a creative way for teaching writing. Based on the data analysis in the previous chapter, the researcher concludes that writing personal letter in teaching recount text was successfully applied by the teacher. Students’ input and appropriate level of material were considered by the teacher, so that it results in students’ interest of learning activity. Moreover, both teacher and students had a good corporation during the teaching and learning process. The students were willing to ask when they have difficulty toward the material given, while the teacher was being a guide during the teaching and learning process The way the teacher teaches writing by providing classroom writing activity which is writing personal letter got positive response from the students. It is supported by the result of students’ works. Overall, students have been able to compose recount text. They have been able to deliver their idea in their writing. The problem appears in the students’ ability in mastering English grammar especially the use of past form. However, with time and regular practice, they will have their best dealing with grammar. SUGGESTION Regarding to the result of the study, the researcher finds that it is necessary to give several suggestion dealing with the teaching recount text using writing personal letter.The teacher has creates an enjoyable condition in teaching writing by using writing personal letter. It results in students’ interest in learn and write recount text. However, we all know that there are students with excellent ability, fair ability, and also poor ability. It is easy enough for those with excellent ability in doing the task given by the teacher, but it will not for those with poor ability. The teacher will not able to help the difficulty of students dealing with the task given since the class has a big amount of students. The teacher should find some strategy or technique that can solve that problem. For further researches, the researcher will recommend further investigation on students’ difficulty dealing with English grammar during the classroom writing activity. Students’ ability in mastering English grammar will influence the quality of their production of text. REFERENCES Ahlsen and Lundh. (2007). Teaching Writing in Theory and Practice. A Study of Ways of Working with Writing in the 9th Grade. Stockholm Institute of Education. Department of Curiiculum Studies and Communication. Al-Jawi, D. F. (2010). Teaching the Receptive Skills: Listening and Reading Skill. Metodhlogy 2.Umm Al Qura University. p.2. Al-Jawi, D. F. (2011). Teaching the Productive Skills in TEFL: Teaching TEFL writing skills. Education and Psychology Department. Umm Al Qura University. p.1-2. Bodomo, A., B. (2002). Quality Education Fund Project. University of Hong Kong. 0384.p.1. Departemen Pendidikan Nasional. (2006). Standart Kompetensi Mata Pelajaran Bahasa Inggris SMP dan Mts. Jakarta: Depdiknas. Gunarwan, Asim. (2000). Globalisation and the Teaching of English in Indonesia. Language in the Global Context: Implications for the Language Classroom. Singapura: SEAMEO Regional Language Centre. Harmer, Jeremy. (____). The Practice of English Language Teaching. Third edition. Longman. Helmi, Farid. (2012). Improving Students Skill in Writing Recount Text by Using Personal Letter (A Classroom Action Research with the Tenth Graders of MASS Proto Pekalongan in the Academic Year of 2011/2012). Thesis. Bachelor Program of English Language Education of State Institute for Islamic Studies Walisongo (IAIN Walisongo). Hendriawati, L. (2011). Writing a Personal Letter to Teach Writing a Recount Text for the Second Grade Students. Unpublished S-1 Thesis. Universitas Negeri Surabaya. Jacob, L. H., et.al. (1981). Testing ESL Composition: A Practical Approach. Newbury House Publishers, Inc. Rowley, Massachusetts 01969. Rowley. London. Tokyo. Langan, John. (2001). Writing Skills with Reading, 5th (ed). New York: Mc. Graw – Hill Companies, Inc. Luchini, P., L. (2003). Writing Skill Teaching: A New Prespective. The Linguistic Association of Korea Journal. 11(3). p.123-143. Marshall, C., and Rossman, G. B. (1995). Designing Qualitative Research (2nd ed). Thousand Oaks, CA: SAGE Publications. Marshall, C., and Rossman, G. B. (1999). Designing Qualitative Research. Thousand Oaks: SAGE Publications. Stockwell, Richard E. (1981). The Stockwell Guide for Technical and Vocational Writing., 2nd edition. California: Addison-Wesley Publishing Company. Suryowati, Fachria, N. (2013). The Implementation of Personal Letter in Teaching Writing of Narrative Text to The Eight Graders of SMP Negeri 5 Sidoarjo. Unpublished Thesis. Advisor: Ririn Pusparini, S.Pd., M.Pd. Pendidikan Bahasa Inggris. Fakultas Bahasa dan Seni. Universitas Negeri Surabaya. Wilson, V. A. (1998) Qualitative Research: An Introduction, Purposes, Methodology, Criteria for Judgment, and a Rationale for Mixed Methodology. Muskingum Collage. Ed 423 285.